BILANGAN RADIO PADA GRAF GEAR - Puspasari, Ambar; Irawanto, Bambang (MATEMATIKA, 2013)
Let d(u,v) denote the distance between two distinct vertices of connected graph G, and diam (G) be the diameter of G. A radio labeling c of G is an assignment of positive integer to the vertices of G satisfying  d(u, v) + |c(u) − c(v)| ≥ diam(G) + 1.The maximum integer in the range of the labeling is its span. The radio number of G, rn(G), is the minimum possible span. Radio number of gear graph G’n , for n ≥ 4  is rn(G’n) ≥ 4n + 2, and n ≥ 7 is rn(G’n) ≤ 4n + 2. The labeling of gear graph G’n , n=4,5,6 is rn(G’4) = 18, rn(G’5) = 22, rn(G’6) = 26 than for n ≥ 4 , the radio number rn(G’n) is  4n + 2.